Catalytic conversion of natural gas with added ethane and LPG over Zn-ZSM-11 - Anunziata, Oscar Alfredo (2000)
The higher hydrocarbons (C2+) from natural gas (NG), such as ethane (C2), propane (C3) and butane (C4) reached excellent levels of conversion over Zn-ZSM-11 at temperatures between 550?640C and 1 atm total pressure, but the methane (C1) present inNG could not be converted. The C1 transformation by activation with co-reactants such as C2 and liquefied petroleum gas (LPG), over Zn-ZSM-11 was studied. The addition of amounts of C2 to a feed of commercial NG allowed to activate the C1 reaching excellent values of conversion and yield to aromatic hydrocarbons (AH). The high Lewis/Bronsted sites ratio of Zn-ZSM-11 catalyst determined by pyridine desorption at different temperatures followed by FT-IR spectroscopy, allowed us to suggest that electron-donor?acceptor complex, formed between C2+ species and unoccupied molecular orbital of the zinc species present in the catalyst, favored the interaction of C2+ through carbenium intermediate to activate methane.